Can indifference make the world greener? - Egebark, Johan; Ekström, Mathias (Journal of Environmental Economics & Management, 2016)
We conducted a natural field experiment to evaluate two resource conservation programs. One intervention consisted of a moral appeal message asking university employees to cut back on printing in general, and to use double-sided printing whenever possible. The other intervention tested whether people׳s tendency to stick with pre-set alternatives is applicable to resource use: at random points in time we changed the default setting on the university printers, from single-sided to double-sided printing. Whereas the moral appeal had no impact, the default change cut paper use by 15 percent. Further analysis adds two important insights. First, we show that defaults influence behavior also in the longer run. Second, we present results indicating that resource efficient defaults have the advantage of avoiding unintended behavioral responses. Overall, our findings send a clear message to anyone concerned about resource conservation: there are potentially large gains to be made from small interventions.